El uso de la tecnología en las actividades comerciales de la Ciudad de Yantzaza - Valle Suquisupa, Jhoana Elizabeth (2024)
Nowadays, the use of technology plays an important role in commercial activities in order to obtain an efficient system that allows counteracting the competitiveness of the market, as well as providing a key factor to obtain progression and success in the commercial environment. The growth of technology has allowed the expansion to reach new clients and optimise commercial operations, which is why it is important to analyse the use of technology in commercial activities in the city of Yantzaza. The methodology applied in the present work of curricular integration adopts a mixed approach, being of transversal type and its descriptive-exploratory scope, given that it is possible to identify factors that positively or negatively affect the use of technological tools for the commercial sector, on the other hand, through a survey applied in a sample of 341 companies, it was possible to collect data on the technological instruments used in the processes of production and sale, in addition to the reasons that drive the disinterest and disuse of the same. The results showed that there is a high percentage of traders using both technological and digital tools for the effective and efficient development of their commercial activities, thus demonstrating that technological advances mean that traders are constantly updating themselves in order to remain in the market and offer greater productivity and competitiveness.